Automatic Blood Pressure Detector Using Arduino to Measure Blood Pressure in Indonesian People Age 19-27 Years Old - ., Ratnadewi; Faizal Ramdhani, Mohammad; Kurniasih, Nuning; Dwi Putri, Lusi; ., Parwito; Abdullah, Dahlan; Listyorini, Tri; Ilham Bakhtiar, Muhammad; Freedom Nanuru, Ricardo; Rahim, Robbi (International Journal of Engineering and Technology, 2018)
No doubt every person wants to be healthy in order to move well. One of the health conditions to note is to keep blood pressure. many people sick one cause is high blood pressure. there are two methods of measuring blood pressure ie invasive and non-invasive. using the oscillometric method the measurement can be performed automatically, with the help of a piezoresistive pressure sensor connected to arduino mega 2560. so that the measurement data in the form of name, age, and blood pressure can be stored on the SD card that can be read again if needed. In this research the difference between the systolic or diastolic values of blood pressure reading with analog devices compared with automatic blood pressure reading tool and obtained that the average difference of 3,265 mmHg for systolic value and 6,165 mmHg for diastolic. Then this difference is used in the calibration process so that the result of automatic blood pressure reading tool is better. The result of calibration reading tool has 99.47% - 99.82% accuracyÂ